1996
DOI: 10.1097/00006534-199609000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Myofascial Flap of the Rectus Abdominus Muscles for the Closure of Recurrent Ventral Hernias

Abstract: Despite a reported incidence of up to 11 percent of incisional/ventral hernias following celiotomies, there is no universally applicable preventive or reconstructive technique in practice. Among patients undergoing repair of ventral incisional herniation, the reported recurrence rates are typically in the 30- to 50-percent range. This study concentrates on the patient with a large, recurrent abdominal incisional hernia in whom conventional surgical repair has failed. We report our recent 4-year experience with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(66 citation statements)
references
References 7 publications
3
58
0
5
Order By: Relevance
“…Many studies have shown that this operation is safe and effective for reconstructing complex abdominal wall defects, with recurrence rates of approximately 10%. [13][14][15][16][17][18] Among our patients, 5 (17%) had postoperative complications, which were all easily treated, and only 1 hernia (3%) recurred.…”
Section: Commentmentioning
confidence: 99%
“…Many studies have shown that this operation is safe and effective for reconstructing complex abdominal wall defects, with recurrence rates of approximately 10%. [13][14][15][16][17][18] Among our patients, 5 (17%) had postoperative complications, which were all easily treated, and only 1 hernia (3%) recurred.…”
Section: Commentmentioning
confidence: 99%
“…The mechanical theory suggests that gas dissects into the bowel wall secondary to disruption in the mucosal integrity due to various factors such as ischemia, trauma or infection [5]. It has also been suggested that gas can tract through the tissues and along the root of the mesentery in patients with COPD [5].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical theory suggests that gas dissects into the bowel wall secondary to disruption in the mucosal integrity due to various factors such as ischemia, trauma or infection [5]. It has also been suggested that gas can tract through the tissues and along the root of the mesentery in patients with COPD [5]. The biochemical theory, on the other hand, proposes that luminal bacteria produce significant amounts of hydrogen as a result of fermentation of mostly carbohydrates, which is then forced into the bowel wall as intraluminal pressure rises.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, Ramirez and Al [6] and Di Bello and Moore [7] already associated dermolipectomy and certain techniques of parietoplasty (in mobilisation by sections and sutures, the various musculo-aponeurotic components). They find respectively a rate of recurrence of 8 and 8.5% [8].…”
Section: Incisional Herniamentioning
confidence: 99%